Costs and cost-effectiveness of treatment setting for children with wasting, oedema and growth failure/faltering: A systematic review. - Noreen Dadirai Mdege; Sithabiso D Masuku; Nozipho Musakwa; Mphatso Chisala; Ernest Ngeh Tingum; Micheal Kofi Boachie; Farhad Shokraneh (Public Library of Science (PLoS), 2023)
This systematic review aimed to address the existing evidence gaps, and guide policy decisions on the settings within which to treat infants <12 months of age with growth faltering/failure, and infants and children aged <60 months with moderate wasting or severe wasting and/or bilateral pitting oedema. Twelve electronic databases were searched for studies published before 10 December 2021. The searches yielded 16,709 records from which 31 studies were eligible and included in the review. Three studies were judged as low quality, whilst 14 were moderate and the remaining 14 were high quality. We identified very few cost and cost-effectiveness analyses for most of the models of care with the certainty of evidence being judged at very low or low. However, there were 17 cost and 6 cost-effectiveness analyses for the initiation of treatment in outpatient settings for severe wasting and/or bilateral pitting oedema in infants and children <60 months of age. From this evidence, the costs appear lowest for initiating treatment in community settings, followed by initiating treatment in community and transferring to outpatient settings, initiating treatment in outpatients then transferring to community settings, initiating treatment in outpatient settings, and lastly initiating treatment in inpatient settings. In addition, the evidence suggested that initiation of treatment in outpatient settings is highly cost-effective when compared to doing nothing or no programme implementation scenarios, using country-specific WHO GDP per capita thresholds. The incremental cost-effectiveness ratios ranged from $20 to $145 per DALY averted from a provider perspective, and $68 to $161 per DALY averted from a societal perspective. However, the certainty of the evidence was judged as moderate because of comparisons to do nothing/ no programme scenarios which potentially limits the applicability of the evidence in real-world settings. There is therefore a need for evidence that compare the different available alternatives.